Impact of synechiae after endoscopic sinus surgery on long-term outcomes in chronic rhinosinusitis - Henriquez, Oswaldo A. (2013)
INTRODUCTION: Synechiae are one of the most common unwanted outcomes after endoscopic sinus surgery (ESS) for chronic rhinosinusitis (CRS). However, there has been scant investigation into the true significance of synechiae formation after ESS. The aim of this study was to evaluate the impact of synechiae formation on quality-of-life (QOL) outcomes after ESS in patients with CRS. STUDY DESIGN: Prospective, multi-institutional cohort. METHODS: Rhinosinusitis Disability Index (RSDI) and Chronic Sinusitis Survey (CSS) scores were measured in adult patients before and after undergoing ESS for CRS. Differences in QOL were evaluated between those who developed sinonasal synechiae and those who did not, controlling for demographic factors, medical comorbidities, and measures of disease severity at baseline. RESULTS: A total of 286 patients underwent ESS, with 55 (19.2%) developing synechiae in the follow-up period. Patients developing synechiae reported significantly less improvement on the RSDI total scores (13.5 vs. 21.4, p=0.008), RSDI physical subscores (5.3 vs. 8.3, p=0.007), RSDI emotional subscores (2.9 vs. 5.8, p=0.008), CSS total scores (14.5 vs. 21.2, p=0.093) and CSS symptom subscores (19.9 vs 30.3, p=0.069) compared to those who did not develop synechiae postoperatively. These differences persisted even after controlling for baseline differences in disease severity. CONCLUSIONS: Synechiae of the sinonasal cavity commonly occurs following ESS, particularly in those undergoing revision surgeries. Although both groups improve, the degree of QOL improvement appears to be less in those who form postoperative synechaie after surgery compared to those who do not.